The Effect of Recruitment and Compensation on Performance Employees of PT Bank BRI Kediri Branch - Rike Selviasari (Program Pascasarjana STIE Amkop Makassar, 2021)
Abstract The purpose of this research is to find out, (1) The effect of Recruitment and Compensation jointly influences employee performance at PT Bank BRI Kediri Branch (2) Effect of Recruitment on employee performance at PT Bank BRI Kediri Branch, (3) Effect of Compensation on employee performance at PT Bank BRI Kediri Branch. The population in this study were all employees at PT Bank BRI Kediri Branch, which amounted to 46 employees. The sampling technique used was the census. The research instruments used were Likert model questionnaires that had been tested for validity and reliability. The data analysis technique used was linear regression. Multiple The results of the study are, (1) Recruitment and Compensation together have a significant effect on employee performance at PT Bank BRI Kediri Branch (2) Recruitment has an effect on employee performance at PT Bank BRI Kediri Branch, (3) Compensation has a significant effect on employee performance at PT Bank BRI Branch of Kediri. Keywords: Recruitment, Compensation, Employee Performance